Biochemical markers of bone turnover in benign paroxysmal positional vertigo. - Sun Bin Lee; Chang Ho Lee; Young Ju Kim; Hyoung-Mi Kim (PLoS ONE, 2017)
Several studies have suggested a possible relationship between recurrent benign paroxysmal positional vertigo (BPPV) and altered calcium homeostasis in the endolymph of the inner ear. The present study aimed to evaluate the association between Ca2+ and vitamin D status and BPPV occurrence as well as the status of bone biochemical markers in osteoporotic patients who were diagnosed with idiopathic BPPV.The study included total 132 patients who were referred to our clinic between August 2008 and October 2013. Based on the bone mineral density (BMD) results, the subjects were divided into three groups: normal BMD (n = 34), osteopenia (n = 40) and osteoporosis (n = 58). The biochemical markers of bone turnover including serum Carboxy-terminal telopeptide of type I collagen (s-CTX), osteocalcin, alkaline phosphatase (ALP) and urinary free deoxypyridinoline (u-DPD), were analyzed, along with the serum Ca2+ and vitamin D levels.The mean serum calcium, phosphate and creatinine clearance levels were within the standard laboratory reference range. The incidence of vitamin D deficiency was 11.8% (4/34) in the normal BMD group, 15% (6/40) in the osteopenia group and 43.1% (25/58) in the osteoporosis group. There was a positive correlation between the 25(OH)D and BMD results in the patients with BPPV. Among the bone turnover markers, the osteocalcin and u-DPD levels were significantly elevated in the osteoporotic patients with BPPV. Multiple logistic regression analyses showed that osteoporosis and vitamin D deficiency were associated with BPPV.Our findings suggest that the prevalence of BPPV in osteoporotic patients is associated with vitamin D deficiency and high bone turnover rates at systemic level, which could disturb local Ca2+ homeostasis in the inner ear.